Dietary Role of Omega - 3 Polyunsaturated Fatty Acid (PUFA): A Study with Growing Chicks, Gallus domesticus - Roy, R.; Singh, S.; Pujari, S. (International Journal of Poultry Science, 2008)
The 7 days old chicks, Gallus domesticus were fed with a diet supplemented with 2.5%, 5% and 10% of ω-3 enriched PUFA (containing 180mg of eciosapentaenoic acid and 120mg docosahexaenoic acid per gram oil) for a period of 30 days. Dietary supplementation of PUFA promotes the growth of the birds that was reflected in the elevation of tissue protein, cholesterol and phospholipid along with a reduction in tissue triglycerides concentrations. Accumulation of ω-3 PUFA along with the depletion of ω-6 PUFA, oleic acid, myristic acid and stearic acid in the tissues was detected. Supplementations of 10% ω-3 enriched PUFA promote the health status of the bird as evident from 20% increase in the haemoglobin concentration of blood, 60% decrease in the serum LDH activity and with no change in the serum cholesterol profiles. 75% reduction in HMG CoA reductase activity along with 62% augmentation of the HMG CoA synthase activity in the liver was recorded which suggest the alteration of cholesterol metabolism in the bird.